FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERANAN PENGURUS BADAN USAHA MILIK PEKON DI PEKON GISTING BAWAH - Bella Aldila; Dewangga Nikmatullah; Tubagus Hasanuddin (Lampung University, 2018)
This research aimed to determine factors that related to the role of BUM Pekon Mandiri Bersatu manager, the changes of customer’s income before and after being a member of BUM Pekon Mandiri Bersatu, and obstacles were impression by BUM Pekon Mandiri Bersatu manager to carry out their duties. The research was conducted on Gisting Bawah Village of Gisting Subdistrict, Tanggamus Regency purposively. The samples of this research were 10 persons of BUM Pekon Mandiri Bersatu manager and 46 customers who is the members of BUM Pekon Mandiri Bersatu. The research data collection was conducted from March 2017 until April 2017. The research data was analyzed descriptively, by Rank Spearman and t test difference. The results showed that: there is definite relationship between human resource quality variable and work environment with the role of manager of BUM Pekon Mandiri Bersatu and there is no definite relationship between customers’ support and wage or salary with the role of manager of BUM Pekon Mandiri Bersatu; there is a change in the customers income level who are members’ of BUM Pekon Mandiri Bersatu between before and after being a members of BUM Pekon Mandiri Bersatu, and obstacles were impression by BUM Pekon Mandiri Bersatu manager were capital and customer complaint problem.Key words: BUM Pekon Mandiri Bersatu, customer, income, management, role